If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 9(y + 6) Reorder the terms: 18 = 9(6 + y) 18 = (6 * 9 + y * 9) 18 = (54 + 9y) Solving 18 = 54 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 18 + -9y = 54 + 9y + -9y Combine like terms: 9y + -9y = 0 18 + -9y = 54 + 0 18 + -9y = 54 Add '-18' to each side of the equation. 18 + -18 + -9y = 54 + -18 Combine like terms: 18 + -18 = 0 0 + -9y = 54 + -18 -9y = 54 + -18 Combine like terms: 54 + -18 = 36 -9y = 36 Divide each side by '-9'. y = -4 Simplifying y = -4
| (x^2-5x+6)=0 | | 3x/7=2x-3 | | 5x/8=9 | | 10x-50+14=36 | | -3x+19=6x+25 | | (3x/4-2) | | 4x-7(x-3)=-36 | | 2Y^2+15Y+10=0 | | 4x^3+5x^2=6-2x | | 4x+3=-6+2x | | 6x-(3-2x)=4-3(8-x) | | 8-3x-6=6.5 | | x+2x+64=148 | | 6.5(n-1)=-4 | | 125=5t^2+30t | | 35t=36 | | 2x-1/x=3 | | 7x+4y=68 | | 3-147=0 | | 45=5t^2+30t | | 5[x-(4x-5)]=7-8x | | x25/21 | | y--1=(2/3)(x-4) | | 5x^2-10=50 | | 1.08(2t+2.50)+3=t | | (2x+5w)(7x-w)= | | Y+5=-3(x-7) | | 14/7*8/7 | | 10-3x4x-5/-3 | | (x/9)=(x/10)-3 | | 10/5*6/8 | | a=11+b |